Avaliação experimental do aumento da transferência de calor e de propriedades térmicas em trocadores de calor utilizando nanofluidos - Saldaña Bernuy, Luis Fernando Junior (2023)
Heat exchangers are devices used to transfer thermal energy between fluids. Their application covers various industrial sectors, including heating, cooling and condensation, the latter being especially important in energy systems. This work aims to evaluate heat transfer in a shell-andtube heat exchanger operating with steam as the hot fluid and water as the cold fluid, which was then replaced by Al2O3 nanofluid. The results show that the heat transfer rate did not change significantly with the use of the nanofluid. However, it can be seen that the nanofluid plays a considerable role in increasing the convective coefficient and the overall average heat transfer coefficients. The thermal conductivity and concentration of the nanoparticles prove to be influential in this phenomenon. It is noteworthy that the most significant increases in the convective heat transfer coefficient are recorded when the steam flow rate is 0.01898 kg/s, showing an increase of 35.9%. In addition, there is also a 34.4% increase when the steam flow rate is increased to 0.02142 kg/s, a 33.1% increase at 0.02262 kg/s and a 32.7% increase when the flow rate reaches 0.02416 kg/s. For the same steam flow rates, the overall average heat transfer coefficients experience notable increases of 31.7%, 30.5%, 29.2% and 28.6%, respectively. It should be noted that the ideal concentration of nanoparticles was determined to be 1.25%, since this concentration provides the highest percentage increases in the variables that influence the heat exchanger's operating parameters.